A systematic review of stress concentration factors (SCFs) in composite reinforced circular hollow section (CHS) joints - Mohsin Iqbal; Saravanan Karuppanan; Veeradasan Perumal; Mark Ovinis; Muhammad Iqbal (Composites Part C: Open Access)
''Composites are an emerging choice for strengthening and repairing compromised structures due to their attractive mechanical properties, environmental durability, and ease of application. After decades of successful use as environmental coatings and for strengthening secondary load members, and with advancements in materials and application techniques, composites are increasingly being used for primary load-bearing components, such as the joints of circular hollow section (CHS) members. The structural stress approach is widely used for the fatigue analysis of CHS joints. This approach utilises stress concentration factors (SCFs) in the joint to determine hot-spot stress, which is then used in conjunction with the respective S-N curve for fatigue life estimation. Composite reinforcement of CHS joints is increasingly being investigated to enhance fatigue life. Various studies have reported a positive impact of composite reinforcement on fatigue strength, either directly or by reducing SCFs in CHS joints. However, certain aspects remain unexplored, while others are frequently revisited. The use of composites for reinforcing tubular joints is systematically reviewed following PRISMA guidelines. Twenty-four articles were selected for detailed study after applying various exclusion and inclusion criteria and removing duplicate records, with eleven, five, three, four, and one articles on T/Y, K, KT, X, and TT-joints, respectively. A critical review of these articles shaped the current understanding of the capabilities of composite reinforcement in CHS joints for enhancing fatigue life and identified areas for future research. These gaps include the investigation of composite reinforcement for joints under combined loads, the optimisation of reinforcement layup, and the development of empirical equations for determining SCFs in various joints under different load configurations.''